ANALISIS KESALAHAN PENGUNAAN PARTIKEL LOKATIF NI, DE, HE, DAN WO MAHASISWA TINGKAT III PENDIDIKAN BAHASA JEPANG UNIVERSITAS RIAU 2013/2014 Studi Kasus Mahasiswa Tingkat III Program Studi Pendidikan Bahasa Jepang FKIP Universitas Riau - Rizal, Ibnu; Aibonotika, Arza; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: The background of writen this research is the mistake of using particle lokatif ni, de, he dan wo at thrird grade university student japanese language education. Function similtary of particle located ni, de, he dan wo often student japanese language make mistake in it applicated. Research was done to get the error higest frequency particles and cause error usage particles.The purpose of this research to get result of knowledge for particle lokatif. The method that use in research is error analysis method language. The result of research with the highest frequency of errors occured in de particles, with stative location marker function.Key words: Error Analysis, Particle, Locative.